Puno and Encinas, among peasant rebellions and education (1895-1910) - Caldas Figuerola, Iván Isaac (2021)
Puno, a region of strong regime subservient and monopoly Catholic in late 19th century and early 20th, lived a social climate that is filled with convulsions and death; peasant rebellions against the gamonalismo. In this scenario was born a school whose intention was to generate a process of inclusion of the indigenous child to become a citizen subject of law. This paper proposes that a young participant in those events, José Antonio Encinas, practiced the anthropological approach, Manuel Gonzales Prada was anticipated to popular schools and there forged a laboratory teaching, secular, rich in values citizens, assimilating Adventist school, early indigenism and the New School.